Pengaruh Kualitas Pelayanan Tenaga Administrasi Rumah Sakit Terhadap Kepuasan Pasien di Unit Instalasi Rawat Jalan Rumah Sakit Umum Daerah Lasinrang Kabupaten Pinrang - Andi Mu’tiah Sari (PPNI UNIMMAN, 2023)
The quality of health services is a level that shows the perfection of health services that can create a sense of satisfaction in each patient. So if there is dissatisfaction with the patient, it is something that needs to be considered. This study aims to determine the effect of the quality of hospital administration services on patient satisfaction in the outpatient installation unit of lasinrang Hospital, pinrang Province. This study uses an analytical observational design based on cross-sectional, quantitative analysis. The population in this study was 10444 patients. The sampling technique used accidental sampling, with a sample of 100 samples. The instrument in this study is a questionnaire, and the data analysis used is simple linear regression.In this study, all indicators of service quality (Tangible, Reliability, Responsiveness, Assurance, Empathy) together have a positive influence on the service quality of hospital administration staff on patient satisfaction in the outpatient installation unit of Lasinrang Hospital, Pinrang Province. There are two service quality indicator variables that have the most dominant influence on the quality of hospital administration staff service on patient satisfaction in the outpatientinstallation unit of Lasinrang Hospital, Pinrang Province, which include the Assurance indicator 48.6% and Tangible 24.3% and (R2) of (0.636) shows that 63.6% of patient satisfaction variables can be explained by the quality of service of hospital administrative staff, while the remaining 36.4% is explained by other variables not included in this research model. So it can be concluded that the better the quality of service, the more satisfied patients will be and will continue to return to get service from time to time because good service can provide satisfaction to patients according to their needs and desires.